ANALYSIS OF WORK FATIGUE AMONG WORKERS IN THE FORMAL AND INFORMAL SECTORS IN CENTRAL JAVA - Haliza, Jihan Syukur Noor; Nugroho, Bayu Yoni Setyo (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Physical and mental fatigue resulting from continuous work over an extended period without sufficient rest. Work fatigue can affect workers in all sectors, both informal and formal, but several factors influence the fatigue levels in each sector. Informal sector workers typically operate in irregular conditions, without fixed working hours, and work for extended periods to meet their livelihood needs. Meanwhile, formal sector workers often have more regular working hours and definite rest periods. However, formal sector workers may also experience similar fatigue due to high job demands, pressure from superiors, or tight deadlines. The consequences of fatigue can lead to serious physical and mental health issues, such as stress, anxiety, sleep disturbances, and even depression. Therefore, it is crucial for workers in both sectors to pay attention to their health and well-being and take measures to prevent fatigue and cope with work-related stress. The research employed a quantitative method with a cross-sectional approach. There were 122 respondents, comprising 61 from the informal sector and 61 from the formal sector. The research findings indicated that the level of fatigue experienced by workers in both sectors was severe, with 78 (63.9%) of informal sector workers predominantly facing this fatigue